PSIKOEDUKASI: UPAYA MENINGKATKAN KEBERMAKNAAN HIDUP WARGA BINAAN DI LEMBAGA PEMASYARAKATAN KELAS 1 MAKASSAR - Muh. Nur Hidayat Nurdin; Andi Ali Syahid; Jirana Humaerah; M Ali Sakti Putra R; Nur Annisa (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2022)
Life inside a correctional institution is of course different from life outside a correctional institution. Many things are impossible to do freely in it. Status as inmates will at least affect the quality and quantity of behavior and interactions between fellow inmates, which of course can affect the meaning of their lives. The purpose of this activity is to provide an understanding of the inmates of the Makassar Class 1 Penitentiary regarding the steps and efforts that can be taken to increase the meaning of life. The implementation method used is through a psychoeducational approach. Psychoeducation is a form of providing education or training to a person or group of people, which aims to provide treatment and rehabilitation. The participants who were included in this psychoeducation activity were 20 people who were fostered by the correctional institution. The provision of pre-test to the inmates of the correctional institution was carried out to measure the level of knowledge and understanding of participants about the meaning of life, and after the provision of psychoeducational material, it was continued with the provision of a post-test to measure whether there was a difference in scores between the pretest and posttest obtained. The results obtained after the provision of psychoeducational materials showed that there was an increase in knowledge and understanding of the meaning of life in the inmates of the correctional institution, which was indicated by an increase in the posttest score when compared to the pretest score that had been previously measured. It can be concluded that the psychoeducational activities carried out are effective in providing knowledge and understanding of the efforts that can be taken by inmates to increase the meaning of their lives while in the Makassar Class 1 Correctional Institution.